Kepemimpinan Mutu Pendidikan di Sekolah Menengah Atas Negeri 4 Batang Hari Provinsi Jambi - Raudatul Janna; Jamaluddin Jamaluddin; Fridiyanto Fridiyanto (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
State High School 4 Batang Hari found the phenomenon that the school has complete educational facilities, supported by Representative Classrooms, Counseling Guidance Room, Multimedia Room, Computer Laboratory, Science Laboratory, Sports Facilities and Prayer Room that supports the learning process. This research uses a qualitative descriptive approach, collecting data through observation, interviews, and documentation. The collected data is analyzed through the process of data reduction, presentation, and conclusion drawn. The results of the research findings show that the Principal Quality Leadership Experience has been applied by the Principal through various activities, namely having previous experience as a Deputy Principal in the curriculum field, always active in the activities of the Teacher Professional organization, having experience in forming teamwork in paying attention to and Have experience in improving the quality of education through the learning process.